Analysis of connection between criminal behavior and psychological traits of perpetrators of criminal offences - Dragan Jovanović (Биомедицинска истраживања, 2018)
Introduction: The aim of the study paper is to examine the relationship between the criminal behavior and psychological traits of perpetrators of criminal offences. Methods: The survey included the prisoners from several Detention and Rehabilitation Centers in the Republic of Srpska as well as from the Judicial Department of the Sokolac Psychiatric Clinic. The sample consisted of 118 offenders divided into two groups: the first group including 60 prisoners who committed the murder and the second group of 58 prisoners who committed other crimes. The second group was further classified into 3 subgroups: robbery perpetrators (N=21), theft perpetrators (N=17) and other criminal offences (N=20). The MMPI-201 (Minnesota Multiphasic Personality Inventory) personality test was used for the purpose of exploring the underlying problem as well as research objectives. Results: The high average scores (>60) were found on the scales of psychopathy, hysteria, schizophrenia, depression and paranoia in the homicide group, while high average values (> 60) were noticed only on psychopathy scale in the non-homicide group. The research showed that mental ilnesses and conditions were more present in the homicide group than in the non-homicide group: antisocial personality disorder was diagnosed in 31.66% of homicides and in 25.86% of non-homicides, which made 28% out of the total number of examinees. Histrionic personality disorder was found in 8.33% of prisoners within the homicide group and in 6.89% of prisoners in the non-homicide group. Schizophrenia was diagnosed in 16.66% of prisoners from the homicide group and in 6.89% of the non-homicide group. Depression was diagnosed in 20% of homicides and in 8.69% of non-homicides. Depression was encountered in comorbidity, usually with antisocial personality disorder. Conclusion: There is a connection between psychological traits and criminal behavior. In homicide group, psychopathological and deviant personality traits are more pronounced, compared with the non-homicide group. Due to this, the former is more likely to develop mental illnesses and conditions.
Keywords: psychological traits; personality; homicides; non-homicides; prisoners